1929
DOI: 10.1085/jgp.13.1.27
|View full text |Cite
|
Sign up to set email alerts
|

The Respiration of Luminous Bacteria and the Effect of Oxygen Tension Upon Oxygen Consumption

Abstract: 1. The respiration of luminous bacteria has been studied by colorimetric and manometric methods. 2. Limulus oxyhaemocyanin has been used as a colorimetric indicator of oxygen consumption and indicator dyes were used for colorimetric determination of carbon dioxide production. 3. The Thunberg-Winterstein microrespirometer has been used for the measurement of the rate of oxygen consumption by luminous bacteria at different partial pressures of oxygen. 4. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1932
1932
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…of Douglas fir when the temperature was restored to its original value after a period of exposure to low temperature (18,19). Furthermore, the rebound effect is also similar to the increase in velocity of oxidation, observed by a number of investigators, when certain tissues and organisms were exposed to oxygen after a period in its absence; nerve (6,5), muscle (5), tomato fruits (7), Planaria (11), and luminous bacteria (25,8). GuSTAFSON (7) also found that, in a given tomato fruit, the magnitude and continuance of increased velocity of oxidation when air was reintroduced into the chamber were dependent upon the length of the period of exposure to pure hydrogen or pure nitrogen.…”
Section: Discussionsupporting
confidence: 75%
“…of Douglas fir when the temperature was restored to its original value after a period of exposure to low temperature (18,19). Furthermore, the rebound effect is also similar to the increase in velocity of oxidation, observed by a number of investigators, when certain tissues and organisms were exposed to oxygen after a period in its absence; nerve (6,5), muscle (5), tomato fruits (7), Planaria (11), and luminous bacteria (25,8). GuSTAFSON (7) also found that, in a given tomato fruit, the magnitude and continuance of increased velocity of oxidation when air was reintroduced into the chamber were dependent upon the length of the period of exposure to pure hydrogen or pure nitrogen.…”
Section: Discussionsupporting
confidence: 75%
“…If we take the extreme values of 12 or 25 mmHg for the oxygen partial pressure (Shoup, 9 Amberson, 10 Fatt, 11 Tang, 12 Takahashi et al 13 ), other values for K m could have been possible. Nevertheless, the Chhabra's value for K m tends to be an estimated average value, and in this way it may be perfectly acceptable.…”
Section: Methodsmentioning
confidence: 99%
“…This technique provides a simple, fast, reliable, and noninvasive way to obtain Q c by wearing a soft contact lens for a few minutes 8. Unfortunately, the current mathematical framework used to obtain Q c from the measured tear‐film oxygen tension is not satisfactory because the oxygen‐consumption rate is assumed constant throughout the cornea; the oxygen‐consumption rate, however, is known to be a nonlinear function of local oxygen tension in biological tissues and organisms 13–21. Further, the corneal oxygen permeability ( D c k c ) needed for obtaining human Q c was measured on rabbits for two corneal layers: endothelium and epithelium 8, 22, 23.…”
Section: Introductionmentioning
confidence: 99%